Uranium hydrogeochemical and stream sediment reconnaissance of the Arctic NTMS quadrangle, Alaska - Shettel, D. L., Jr.; Langfeldt, S. L.; Youngquist, C. A.; D'Andrea, R. F., Jr.; Zinkl, R. J. (comps.) (Bendix Field Engineering Corporation, 1981)
This report presents results of a Hydrogeochemical and Stream Sediment Reconnaissance (HSSR) of the Arctic NTMS quadrangle, Alaska. In addition to this abbreviated data release, more complete data are available to the public in machine-readable form through the Grand Junction Office Information System at Oak Ridge National Laboratory. Presented in this data release are location data, field analyses, and laboratory analyses of several different sample media. For the sake of brevity, many field site observations have not been included in this volume. These data are, however, available on the magnetic tape. Appendix A describes the sample media and summarizes the analytical results for each medium. The data were subdivided by one of the Los Alamos National Laboratory (LANL) sorting programs of Zinkl and others into stream sediment samples. For the group which contains a sufficient number of observations, statistical tables, tables of raw data, and 1:1000000 scale maps of pertinent elements have been included in this report. In addition, maps showing results of multivariate statistical analyses have been included. Further information about the HSSR program in general, or about the LANL portion of the program in particular, can be obtained in quarterly or semiannual program progress reports on open-file at DOE's Technical Library in Grand Junction. Information about the field and analytical procedures used by LANL during sample collection and analysis may be found in any HSSR data release prepared by the LANL and will not be included in this report.